1993
DOI: 10.1128/iai.61.11.4902-4905.1993
|View full text |Cite
|
Sign up to set email alerts
|

P1-antigen-containing avian egg whites as inhibitors of P adhesins among wild-type Escherichia coli strains from patients with urosepsis

Abstract: Among 58 Escherichia coli urosepsis isolates, Pl-antigen-containing dove and pigeon egg whites were significantly more effective inhibitors of P-adhesin-specific agglutination than were chicken egg whites or globoside. Globoside's inefficacy may have resulted from a proadherence effect of globoside's lipid tail. Adhesin phenotypes determined with dove and pigeon egg whites as agglutination inhibitors corresponded closely with phenotypes defined by comparative hemagglutination of human P1 and p erythrocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Prior to experiment 2, to exclude strains with non-P adhesins, microscope slide HA assays (24) were used to determine each strain's mannose-resistant HA (MRHA) titer for human A 1 P 1 and p erythrocytes ( Table 2). If HA was observed with either cell type, inhibition of HA by pigeon egg white (PEW) and 3% bovine serum albumin (Sigma) in PBS was assessed at a bacterial concentration four times that required for HA (19,20). Strains that exhibited PEW-inhibitable MRHA of A 1 P 1 erythrocytes but no MRHA of p erythrocytes were considered to express P adhesins; those that exhibited PEW-inhibitable MRHA of both A 1 P 1 and p erythrocytes were considered to express NPMR (formerly X) adhesins (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to experiment 2, to exclude strains with non-P adhesins, microscope slide HA assays (24) were used to determine each strain's mannose-resistant HA (MRHA) titer for human A 1 P 1 and p erythrocytes ( Table 2). If HA was observed with either cell type, inhibition of HA by pigeon egg white (PEW) and 3% bovine serum albumin (Sigma) in PBS was assessed at a bacterial concentration four times that required for HA (19,20). Strains that exhibited PEW-inhibitable MRHA of A 1 P 1 erythrocytes but no MRHA of p erythrocytes were considered to express P adhesins; those that exhibited PEW-inhibitable MRHA of both A 1 P 1 and p erythrocytes were considered to express NPMR (formerly X) adhesins (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Egg whites of pigeons, doves, and members of the parrot family exhibit high levels of the digalactoside-containing PI antigen and they are potent inhibitors of P adhesins from E. coli 596 (Johnson et al 1992). Albeit P-fimbriae of strain J96 are not representative of the P adhesins of most uropathogenic strains (Striimberg et al 1990), Johnson & Ross (1993) have found that avian P1-antigen-containing glycoproteins strongly inhibit P adhesins of wild-type E. coli strains from patients with urosepsis. These data correlate with the results obtained in the present research which have shown that P,-antigen-containing pigeon egg white inhibits the adherence of wild-type P-fimbriated E. coli strains isolated from the urine of patients with uroinfection to BGM cells, as well as hemagglutination caused by these strains.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were considered to express P-fimbriae if HA was positive with human erythrocytes and inhibition of HA was positive with pigeon egg white, which was confirmed by agglutination of receptorcoated latex beads (Johnson & Ross 1993). Isolates were considered to express ONAP (0 negative, A positive) adhesin if they agglutinated sheep and human Alpl erythrocytes but did not agglutinate human OPI MM, OplNN, OP2MM, OP2NN erytrocytes and Gal-Gal-latex beads, and to express an X-adhesin if they agglutinated human erythrocytes but not Gal-Gal-latex beads (Lindstedt et al 1989).…”
Section: Determination Of Bacterial Adhesinsmentioning
confidence: 99%